2019
DOI: 10.1002/jcc.26064
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Methods for Modeling Covalent Modification of Biological Thiols

Abstract: Targeted covalent inhibitor drugs require computational methods that go beyond simple molecular‐mechanical force fields in order to model the chemical reactions that occur when they bind to their targets. Here, several semiempirical and density‐functional theory (DFT) methods are assessed for their ability to describe the potential energy surface and reaction energies of the covalent modification of a thiol by an electrophile. Functionals such as PBE and B3LYP fail to predict a stable enolate intermediate. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 106 publications
0
63
0
Order By: Relevance
“… 26 The 1,2-addition pathway, consisting of a direct PT from the thiol to the α-carbon of the acrylamide warhead and simultaneous S–C formation has been reported as a high energy pathway by Rowley et al who calculated the barrier of the 1,2-σ addition of methylvinyl ketone and methyl thiolate to be 65.2 kcal mol −1 at the CCSD(T)//ωB97X-D level. 27 QM/MM simulations of 1,2-addition in BTK suggested a very high barrier (approximately 47.7 kcal mol −1 ), and we therefore discounted it as a feasible mechanism based on our simulations and the findings of Rowley et al We also investigated the solvent-assisted variant of this pathway, but the free energy surface did not represent a feasible reaction pathway: we observed additional PTs that indicated a strong preference for the reaction to proceed via an enol intermediate (see ESI for details † ).…”
Section: Resultsmentioning
confidence: 99%
“… 26 The 1,2-addition pathway, consisting of a direct PT from the thiol to the α-carbon of the acrylamide warhead and simultaneous S–C formation has been reported as a high energy pathway by Rowley et al who calculated the barrier of the 1,2-σ addition of methylvinyl ketone and methyl thiolate to be 65.2 kcal mol −1 at the CCSD(T)//ωB97X-D level. 27 QM/MM simulations of 1,2-addition in BTK suggested a very high barrier (approximately 47.7 kcal mol −1 ), and we therefore discounted it as a feasible mechanism based on our simulations and the findings of Rowley et al We also investigated the solvent-assisted variant of this pathway, but the free energy surface did not represent a feasible reaction pathway: we observed additional PTs that indicated a strong preference for the reaction to proceed via an enol intermediate (see ESI for details † ).…”
Section: Resultsmentioning
confidence: 99%
“…Transition state optimization with the ωB97X-D functional was found to be significantly more reliable, and recently published work has shown that ωB97X-D is better suited to describing acrylamide reaction energetics relative to a CCSD(T) reference. 11 For these reasons, IEFPCM-ωB97X-D/6-311+G(d,p) was used for all calculations unless otherwise noted.…”
Section: ■ Computational Discussionmentioning
confidence: 99%
“…2-(Morpholinomethyl)-N-phenylacrylamide (11). Compound 11 was made according to the procedure for 10 using morpholine in place of dimethylamine.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…† This result conrms the adequacy of the B3LYP functional for the present Michael addition, in spite of the reported limitations of this functional to correctly describe some enolate or carbanion intermediates. 23,24 Note that these species are not strictly found in the proposed mechanism because of the proton transfer from His41 to the substrate. It must be also stressed that at both theoretical levels, the string converges to a mechanism evolving from the IP to the covalent product, conrming that, in agreement with our previous work, 10 the IP is a metastable species from which the most favorable mechanism may proceed.…”
Section: Formation Of the Covalent E-i Complexmentioning
confidence: 99%